TECHNOLOGIES FOR STORING AND QUERYING LARGE COLLECTIONS OF XML DOCUMENTS (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2023)
Currently, web applications using XML repositories (banking, accounting, personnel management, airline reservations, weather monitoring and forecasting, electronic control and e-commerce) process a huge amount of temporary information and need a complete history of data and schema changes for effective and transparent management of the information system. Existing XML DBMS and XML tools do not support this function, which makes it difficult to build a history of changes, difficult to return to the previous state, and the possibility of data loss. As a result, there is a problem of effective management of temporary data storage when working with a large number of small XML documents and many additional elements /attributes.
Keywords: русский